VEKTOR AUTO-REGRESI: CATATAN HISTORIS DAN PENGEMBANGAN - Mohtar Rasyid (Trunojoyo University of Madura, 2015)
The purpose of this paper is to describe the development of econometric time-series modeling from early development to contemporary issues. Economic structural model begins with the Keynesian macro model with a simple equation system to a system with hundreds of equations. One interesting issue in the econometric modeling of time series stationarity issue is the emergence of the new standards in advanced econometric analysis. The model system with a new approach known as VAR with emphasis in the data: let the data speak (let's Data talk). This model has become the new standard with variations VECM and several derivative models. This paper concludes with a brief discussion of new approaches to discuss the adjustments that are non-linear.